Pathological Downstaging and Survival Outcomes Associated with Neoadjuvant Chemotherapy for Variant Histology Muscle Invasive Bladder Cancer. Issue 4 (25th October 2021) - Chakiryan, Nicholas H.; Jiang, Da David; Gillis, Kyle A.; Green, Elizabeth; Hajiran, Ali; Hugar, Lee; Zemp, Logan; Zhang, Jingsong; Jain, Rohit; Chahoud, Jad; Poch, Michael; Manley, Brandon J.; et al.
Abstract : Purpose: Patients with muscle invasive bladder cancer (MIBC) of variant histology have a poor prognosis. It is unclear if neoadjuvant chemotherapy prior to radical cystectomy is associated with pathological downstaging or improved overall survival (OS) for patients with variant histology. Our objective was to assess for associations between receipt of neoadjuvant chemotherapy, pathological downstaging and OS for patients with variant histology MIBC. Materials and Methods: Patients were identified in the National Cancer Database from 2004 to 2017 with MIBC, without metastases, who underwent radical cystectomy. Patients were stratified by histological subgroup, and receipt or nonreceipt of neoadjuvant chemotherapy. Pathological downstaging was defined as pT0N0 or pT ≤1N0, and OS from the time of diagnosis to date of death or censoring at last followup. Multivariable logistic regression analysis determined associations between neoadjuvant chemotherapy and pathological downstaging. Multivariable Cox regression analysis determined associations between neoadjuvant chemotherapy and OS. Results: A total of 31, 218 patients were included in the final study population (urothelial carcinoma [UC]: 27, 779; sarcomatoid UC: 501; micropapillary UC: 418; squamous cell carcinoma: 1, 141; neuroendocrine carcinoma: 629; adenocarcinoma: 750). Neoadjuvant chemotherapy was associated with pathological downstaging to pT0N0 in all histological subgroups (UC: OR 5.1 [4.6–5.6]; sarcomatoid UC: OR 13.8 [5.5–39.0]; micropapillary UC: OR 9.7 [2.8–46.8]; squamous cell carcinoma: OR 7.4 [2.1–24.5]; neuroendocrine: OR 4.7 [2.6–9.2]; adenocarcinoma: OR 23.3 [8.0–74.2]). Neoadjuvant chemotherapy was associated with improved OS for UC (HR 0.8 [0.77–0.84]), sarcomatoid UC (HR 0.64 [0.44-0.91]) and neuroendocrine carcinoma (HR 0.55 [0.43–0.70]). Conclusions: Neoadjuvant chemotherapy was associated with pathological downstaging for all MIBC histological variants, with improved OS for patients with UC, sarcomatoid variant UC and neuroendocrine carcinoma.